Sago starch and its acrylamide modified products as coating material on handsheets made from recycled pulp fibers - Sin Yeng, Wong; Paridah, Md. Tahir; Liew, Kang Chiang; Wan Md. Zin, Wan Yunus; Sarani, Zakaria (Wiley Periodicals, Inc, 2004)
This study was carried out to determine the suitability of sago starch as a paper additive. The basic properties (i.e., pH, viscosity, and solid content) of the 5% weight over volume basis of unmodified and modified sago starch (sago starch blended with acrylamide, sago starch grafted with acrylamide in an acidic and adjusted to alkaline conditions) were determined. The starches were then used to coat laboratory handsheets made from recycled pulp fibers. The incorporation of acrylamide into sago starch through grafting significantly reduced the viscosity of the solution. Generally, coating the handsheets with unmodified sago starch significantly improved some properties as compared to the uncoated handsheets. Among the three types of sago starch modification methods, blending gave superior performance when coated on the handsheets, except for smoothness and air permeance, due to insufficient curing shown by the micrographs. FTIR spectra showed that the interactions between the blended acrylamide–starch solutions and the pulp fiber were weak. © 2004 Wiley Periodicals, Inc. J Appl Polym Sci 94: 154 –158, 2004.